The effect of exercises special assistance in the development of motion speed and performance of movement of the player - Mohamed, Omar (Journal of Physical Education, 2012)
The first chapter presents the development in the field of athletic training through the use of manners and methods that contribute to the development of players. As is the importance of research in the use of exercises similar to the circumstances of the race to development performance of some offensive skills composite basketball. The problem lies in prepare of skills which did not take the real role and size in the training process according to the circumstances of private competition in a game of basketball. They also indicate to the aims of the research and hypothesis as well as areas of research. In second chapter, the researchers dealt with some of the theoretical topics and methods of training skills composite in the basketball. In third chapter, the researchers used the experimental method on a sample of (8) players from Sulaikh club for youth and included one experimental group. The study, in chapter fourth, presents the results were discussed and analyzed through the use of a number of statistical tools, which the researchers to an evolution in the performance of some offensive skills composite basketball. Finally, in chapter five, the conclusion indicates that the skills training by training a low intensity has been a very effective in the development of performance skills, as well as the researcher presents recommendation for time from the days of training to development basic skills and composite skills as well as the need for attention from the presence of coaches training of skills throughout the year.